PERUBAHAN PENGETAHUAN DAN SIKAP WANITA YANG MEMILIKI PASANGAN TERHADAP PEMERIKSAAN PAP SMEAR SEBELUM DAN SESUDAH DIBERIKAN PENYULUHAN TENTANG DETEKSI DINI KANKER SERVIKS DENGAN PEMERIKSAAN PAP SMEAR DI KELURAHAN GLUGUR DARAT I KECAMATAN MEDAN TIMUR KOTA - Rosmala Dewi; Asfriyati .; Abdul Jalil Amri Arma (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Cervical cancer is a disease that causes malignant gynecologic problems in women’s health. Pap smear is a microscopic examination that can detect cancer cells. The earlier the cancer cells are detected, the lower the risk of women who have a spouse suffering from cervical cancer. In fact, women who have a partner are still not aware of the importance of pap smears, due to low level of knowledge, lack of access to information and lack of response to a pap smear. This research is a quasi experiments with the approach one group pretest-posttest. The population in this study are all women who have a partner who has never done a pap smear and lived in Kelurahan Glugur Darat I then selected an accidental sampling and obtained a sample of 72 respondents. The statistical test used was the Wilcoxon test. Before the extension 50 respondents had a good knowledge and 22 have sufficient knowledge. After the extension 72 respondents had a good knowledge. Before the extension 24 respondents have a good attitude and 48 have enough attitude. After the extension 67 respondents have a good attitude and 5 have enough attitude. There are changes in knowledge and attitudes of women who have a partner for a pap smear before and after giving information to the value of p = 0.0001. Health workers are expected to do counseling about cervical cancer and pap smears to improve knowledge and attitudes so that women who have a partner willing to do a pap smear. Key word: pap smear, knowledge and attitude